Renal Replacement Therapy in Critically Ill: Current Trend and New Direction (Bangladesh Critical Care Journal, 2015)
Critically ill patients often present with renal dysfunction. Acute kidney injury (AKI) is common in intensive care unit (ICU) patients and is often a component of multiple organ dysfunction syndrome (MODS). Renal replacement therapy (RRT) plays a significant role in management of acute and chronic renal failure in ICU. During the last decade RRT has made remarkable progress in management of renal dysfunction of critically ill. The Acute Dialysis Quality Initiative conceived in 2002 proposed RIFLE classification for AKI (risk, injury, failure, loss, end-stage kidney disease) using serum creatinine and urine output in critically ill patients. More recently, the Acute Kidney Injury Network (AKIN) has been introduced for staging AKI. Studies have shown that mortality increases proportionately with increasing severity of AKI. In patients with severe AKI requiring RRT mortality is approximately 50% to 70% according to one study and even a small changes in serum creatinine are associated with increased mortality. The most common causes of AKI in ICU are sepsis, hypovolemia, low cardiac output and drugs. The various techniques of RRT used in ICU include intermittent hemodialysis (IHD), continuous RRT (CRRT), sustained low efficiency dialysis (SLED) and peritoneal dialysis (PD). It is preferable to use RRT at either RIFLE injury type or at AKIN stage II in critically ill patients. IHD is commonly used in hemodynamically stable ICU patients. Because of high dialysate (500ml/min) IHD may cause hypotension in some patients. Solute removal may be episodic and often result in inferior uraemic control and acid base control. CRRT is usually initiated with a blood flow of 100 to 200 ml/min. and thus hemodynamic instability associated with IHD is avoided. Major advantages of CRRT include continuous control of fluid status, hemodynamic stability and control of acid base status. It is expensive and there is high risk of bleeding because of use of high dose of IV heparin. SLED has been found to be safe and effective in critically ill patients with hemodynamic instability. It uses the same dialysis machine of IHD and combines the effectiveness of CRRT in unstable patients and easy operability of IHD. It is also cost effective. PD is initiated in ICU for AKI patients when bedside IHD is not available. It is good for hemodynamically unstable patients when IHD or CRRT is difficult. In patients on mechanical ventilator, PD interferes with function of diaphragm causing decrease in lung compliance. Early identification of AKI with bio markers is an important step in improving outcomes of AKI. These bio markers help early detection of AKI before the onset of rise in serum creatinine. Serum cystatin C is one of the sensitive bio markers of small changes in Glomerular filtration rate (GFR) and has been found to be useful. AKI in the ICU most commonly results from multiple insults. Therefore appropriate and early identification of patients at risk of AKI provides an opportunity to prevent subsequent renal insults. This strategy will influence overall ICU morbidity and mortality.Bangladesh Crit Care J March 2015; 3 (1): 17-21